2012
DOI: 10.18869/acadpub.3dj.1.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic Study of Benign Soft Tissue Tumors of Oral Cavity in an Iranian Population

Abstract: Introduction: Few studies on benign soft tissue tumors of oral cavity have been conducted in an Iranian population. The purpose of this study was to evaluate the prevalence of the benign soft tissue tumors of the oral cavity in three central pathology centers of Rasht, Iran. Materials and Methods:In this retrospective study, all benign soft tissue tumors of the oral cavity, were retrieved from Razi, Afrah and Poursina Hospital Pathology Laboratories during 2000 to 2008, and demographic data for each case was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 10 publications
(24 reference statements)
1
9
0
6
Order By: Relevance
“…12 Shahsavari et al found Pyogenic granuloma as the most common benign oral lesion. 13 In present study most common site of involvement amongst benign oral lesions was buccal mucosa comprising 50.6% of all cases, which is comparable with studies by Agarwal et al, Modi et al and Kosam et al, Al Khateeb et al and Shahsavari et al found gingiva as most common site of benign oral lesions. 3,11,[13][14][15] Esent study oral sub mucus fibrosis was most commonly found in younger age group 21-30 years and found predominantly in males.…”
Section: Discussionsupporting
confidence: 91%
“…12 Shahsavari et al found Pyogenic granuloma as the most common benign oral lesion. 13 In present study most common site of involvement amongst benign oral lesions was buccal mucosa comprising 50.6% of all cases, which is comparable with studies by Agarwal et al, Modi et al and Kosam et al, Al Khateeb et al and Shahsavari et al found gingiva as most common site of benign oral lesions. 3,11,[13][14][15] Esent study oral sub mucus fibrosis was most commonly found in younger age group 21-30 years and found predominantly in males.…”
Section: Discussionsupporting
confidence: 91%
“…Hemangioma is most common in the head and neck regions, but is rare in the oral cavity. It accounts for 10.2% of benign tumors, and has been found to range from 6.5% to 39.5% in previous studies . It is distributed equally between the sexes.…”
Section: Discussionmentioning
confidence: 92%
“…The Jazan region stretches approximately 300 km along the southern Red Sea coast, just north of Yemen, covering an area of 11 671 km² and approximately 1 109 590 people. Most of the studies on benign orofacial tumors have focused either on soft tissue tumors, which include reactive lesions, as well as benign tumors or benign jaw tumors . Benign orofacial tumors accounted for 10.9% of oral biopsies, which is comparatively less than the 18.4% reported by Shahsavari et al .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…These consist of tumours made up of fibrous tissue, fat, muscle, nerves and blood vessels. [1] In oral cavity, mastication makes it susceptible for different types of trauma and injury, also the presence of teeth and odontogenic tissue is adding more liability for variety of diseases which vary from, simple inflammatory disease to highly malignant tumours. [2] Tumourlike lesions of oral cavity are not included in the WHO classification 2005.…”
Section: Introductionmentioning
confidence: 99%